The metabolism of folic acid in pregnancy toxemia - Soberon Acevedo, Javier (2015)
A comparative study of the metabolism of folic acid has been made in two groups: 16 normal pregnant women and 74 women with toxemia of pregnancy; in this group an increased excretion of formiminoglutamic acid was observed, indicating a deficiency of folic acid; this phenomenon was normalized by the administration of folic acid. These results demonstrate that in patients with toxemia of pregnancy there is a deficiency of folic acid, but do not establish the relationship between both.